Never Tell : A Novel - Gardner, Lisa; Potter, Kirsten ([Grand Haven, Michigan] : Brilliance Audio, 2019)
A man is dead, shot three times in his home office. But his computer has been shot twelve times, and when the cops arrive, his pregnant wife is holding the gun. D.D. Warren arrives on the scene and recognizes the woman, Evie Carter, from a case many years back. Evie's father was killed in a shooting that was ruled an accident. But for D.D., two coincidental murders is too many.
Keywords: Warren, D. D. (Fictional character) -- (Fictitious character) -- Fiction; Women detectives -- Fiction -- Massachusetts; Police -- Fiction -- Massachusetts; Pregnant women -- Fiction; Murder -- Fiction -- Investigation; Family secrets -- Fiction; FICTION / Thrillers / Suspense; FICTION / Thrillers / Crime; FICTION / Mystery & Detective / Police Procedural; Boston (Mass.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Psychological fiction; Audiobooks